Multi-Compartment and Multi-Host Vector Suite for Recombinant Protein Expression and Purification - Ortega, Claudia; Prieto, Daniel; Abreu, Cecilia; Oppezzo, Pablo; Correa, Agustín (Frontiers in Microbiology, 2018)
Recombinant protein expression has become an invaluable tool in basic and applied research. The accumulated knowledge in this field allowed the expression of thousands of protein targets in a soluble, pure and homogeneous state, essential for biochemical and structural analyses. A lot of progress has been achieved in the last decades, where challenging proteins were expressed in a soluble manner after evaluating different parameters such as host, strain, and fusion partner or promoter strength, among others. In this regard, we have previously developed a vector suite that allows the evaluation of different promoters and solubility enhancer-proteins, through an easy and efficient cloning strategy. Nonetheless, the proper expression of many targets remains elusive, requiring for example the addition of complex post-translation modifications and/or passage through specialized compartments. In order to overcome the limitations found when working with a single subcellular localization and a single host type, we herein expanded our previously developed vector suite to include the evaluation of recombinant protein expression in different cell compartments and cell hosts. In addition, these vectors also allow the assessment of alternative purification strategies for the improvement of target protein yields.